The British publishing industry in the Nineteenth Century.
1 online resource (xxvi, 430 pages)
Keywords: This volume brings together key documents covering technologies of production that affected the British publishing industry during a significant period of change. It focuses in particular on key source material related to industrialisation of print production, which saw major leaps forward as mechanised innovations increased the speed, efficiency and delivery of texts through the production process. The introduction of iron, steam and other forms of rotary power presses improved the output of the print room over the century. Alongside this came improvements in typesetting and associated tasks, with the adoption of linotype and monotype casting machines. Changes in available methods of reproducing illustrations such as the development of lithographic printing processes and, in the second half of the century, photographic processes such as half-tone and photogravure, enabled wider incorporation of illustrations into periodicals and books. Such technological changes also fed organisational changes within the print and publishing trade. National unions for the print trade were established in the middle of the century to adapt to new working conditions, and engaged in robust debates about technology and its effect in the workplace.